Economic Monitoring of Transformation Processes: National Realities and Foreign - INNA IRTYSHCHEVA; Yevheniya Boiko; OLENA PAVLENKO; Iryna Kramarenko; KSENIIA CHUMAKOVA; NATALIA HRYSHYNA; OLENA ISHCHENKO; ANASTASIIA ZUBKO (International Journal of Industrial Engineering and Production Research, 2023)
The research is devoted to the theoretical and applied